1999
DOI: 10.1002/(sici)1097-0010(19990301)79:3<373::aid-jsfa257>3.3.co;2-y
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxycinnamic acids in the digestive tract of livestock and humans

Abstract: Hydroxycinnamic acids are consumed as water-soluble conjugates and in larger amounts bound to plant cell walls. Bound acids are primarily released by microbial action in the modiüed forestomach of ruminants and the hindgut of non-ruminant species, including humans. In the rumen, rapid hydrogenation of p-coumaric, ferulic and caþ eic acids, followed by dehydroxylation at C4 and more slowly at C3 yields 3-phenylpropionic acid. Phenylpropionate is absorbed and undergoes boxidation in the liver to benzoic acid whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
91
0
5

Year Published

2000
2000
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(101 citation statements)
references
References 8 publications
(8 reference statements)
5
91
0
5
Order By: Relevance
“…Our research demonstrates that both bermudagrass and supina bluegrass are rich sources of phenolic compounds, notably free ferulic acid. Simple phenolic acids are among the most highly consumed and bioavailable classes of phenolic compounds (Smith and Hartley, 1983;Chesson et al, 1999;Anson et al, 2009). This work also shows that the free phenolic compositions of select Poaceae seedlings change over the course of seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…Our research demonstrates that both bermudagrass and supina bluegrass are rich sources of phenolic compounds, notably free ferulic acid. Simple phenolic acids are among the most highly consumed and bioavailable classes of phenolic compounds (Smith and Hartley, 1983;Chesson et al, 1999;Anson et al, 2009). This work also shows that the free phenolic compositions of select Poaceae seedlings change over the course of seedling growth.…”
Section: Resultsmentioning
confidence: 99%
“…Although not lignified, these cell walls are only slowly and partially degraded by bacterial enzymes in rat and human large intestines [39 -41]. In addition to the feruloyl and pcoumaroyl groups, the ferulic acid dehydrodimers are also released from cell walls following microbial degradation [42]. However, the concentrations of ferulic acid dehydrodimers in aleurone cell walls are low [38].…”
Section: Discussionmentioning
confidence: 99%
“…Cell wall release may lead to the compounds being more bioavailable in the colon than if the isolated compound is fed directly to animals or humans. Thus, for example, although rats fed ferulic acid displayed no changes in hepatic CYP levels [42], the regime used may not have resulted in such high levels in the colon as could be achieved through release of the acid from plant cell walls.…”
Section: Discussionmentioning
confidence: 99%
“…Esterase activity has been found in the gut microflora of animals and humans 77. 79 There are no reports of intact native conjugates in plasma or urine, although it has been shown that various CGA enter cultured T‐lymphoblasts80, 81 and cultured human hepatoma cells 82…”
Section: Cinnamates In Foods and Beveragesmentioning
confidence: 99%